2015
DOI: 10.3923/jest.2015.300.309
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Study on Human Health and Safety Loss for Rural and Urban Areas in Monetary Value Subjected to Gas Pipeline Failure

Abstract: Consequence assessment is an integral part of the risk assessment process carried out by the industry to minimize impact of assets failure on the environment, human safety, assets integrity and business reputation. A few components of consequences loss occur due to the pipeline failure, such as asset loss, environmental loss, production loss, public loss and Human Health and Safety Loss (HHSL). This study focuses on HHSL by considering the losses in term of monetary value between rural and urban areas due to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In order to evaluate the risks associated with natural gas pipelines, the possible undesirable consequences that may arise from any pipeline leak or rupture. As examples from the previous studies [10,14,16,17], the consequences of possible accidents were determined using the ALOHA program. In addition, in the study conducted by Zhou et al [14], land use modifications were suggested for the risk areas, which are determined around the pipeline.…”
Section: Threat Distances For Worst Case Scenariomentioning
confidence: 99%
See 1 more Smart Citation
“…In order to evaluate the risks associated with natural gas pipelines, the possible undesirable consequences that may arise from any pipeline leak or rupture. As examples from the previous studies [10,14,16,17], the consequences of possible accidents were determined using the ALOHA program. In addition, in the study conducted by Zhou et al [14], land use modifications were suggested for the risk areas, which are determined around the pipeline.…”
Section: Threat Distances For Worst Case Scenariomentioning
confidence: 99%
“…Bajcar et al [15] provided a refined way to measure the effects of third-party interventions on the risk to people posed by natural gas transmission pipelines. Hanafiah et al [16] calculated and compared the human health and safety loss as a result of natural gas pipeline failures in monetary terms for rural and urban sites. For this purpose, they determined a fire scenario leading to a vapor cloud explosion and calculated the damage radiuses using the ALOHA program for this scenario.…”
Section: Introductionmentioning
confidence: 99%